Septic Arthritis Caused by Mycobacterium Kansasii in a Bone Marrow Transplant Recipient. Issue 8 (November 2020) - Sugiyama, Minako; Terashita, Yukayo; Hara, Kazuya; Cho, Yuko; Asano, Tsuyoshi; Iguchi, Akihiro
Abstract : We report an 18-year-old female individual with septic arthritis due to Mycobacterium kansasii. Three years and 6 months before arthritis, the patient underwent bone marrow transplantation and developed severe chronic graft-versus-host disease. The arthritis was refractory to medication, and she underwent joint lavage of the right foot, hip joint, and elbow joint. After surgery, her joint symptoms were relieved, and chronic graft-versus-host disease remitted more easily. It is important that we maintain a high index of suspicion for mycobacterial arthritis and diagnose it early when immunosuppressed patients experience chronic pain and joint swelling.